1 William Waller Hening, The Statutes at Large: Being a Collection of all the Laws of Virginia 198 (1809) - (:unkn) unknown (My University, 1632)
"NOE man shall goe to worke in the grounds without theire armes, and a centinell uppon them places where the commander shall require it." And "ALL men that are fittinge to beare armes, shall bringe their peices to the church"
Keywords: REQUIRED POSSESSION; CARRY - CERTAIN PUBLIC PLACES; SENSITIVE PLACES